2012
DOI: 10.52283/nswrca.ajbmr.20120206a02
|View full text |Cite
|
Sign up to set email alerts
|

ENERGY CONSUMPTION AND ECONOMIC GROWTH: Evidence from Pakistan

Abstract: This paper investigates the relationship between energy consumption and economic growth of Pakistan. A time series data has been used for the period of 1973-2006. GDP is taken as dependent variable and energy consumption as independent variable. Augmented Dicky Fuller test has been used to check the stationary of the variables and both variables found stationary at level. The results of Granger causality test show uni-directional causality running from GDP to energy consumption. The results of ordinary least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…There is need for appropriate interest rate policy, taken into cognizance the investment climate and the targeted sector of the economy, in order to encourage private investment and expansion in the size of the market and the enhancement of purchasing power of the people are also needed to encourage private investment in the services sector. The study agrees with Ahmad et al (2012) who examined the effect of government spending and macro-economic uncertainty on private investment in service sector for the period 1972 to 2005 and found that government recurrent expenditures mostly appeared as substitutes to private investment and affect private investment in services negatively in the long run.…”
Section: Factors Affecting Government Agricultural Expenditure In The...supporting
confidence: 88%
“…There is need for appropriate interest rate policy, taken into cognizance the investment climate and the targeted sector of the economy, in order to encourage private investment and expansion in the size of the market and the enhancement of purchasing power of the people are also needed to encourage private investment in the services sector. The study agrees with Ahmad et al (2012) who examined the effect of government spending and macro-economic uncertainty on private investment in service sector for the period 1972 to 2005 and found that government recurrent expenditures mostly appeared as substitutes to private investment and affect private investment in services negatively in the long run.…”
Section: Factors Affecting Government Agricultural Expenditure In The...supporting
confidence: 88%
“…On the other hand, they applied Granger causality to find out the direction of causality between energy consumption and economic growth and explored that both short term and long term changes in economic growth cause changes in energy consumption. Ahmad, Hayat, Hamad and Luqman (2012) conducted research to determine the relationship between economic growth and energy consumption in Pakistan. A positive relationship has been found between Gross Domestic Product and Energy Consumption for Pakistan.…”
Section: Reviews From Pakistan Economymentioning
confidence: 99%
“…The study adopted a simple model relating the variables under investigation and employed a simple theoretical framework of the Cobb Douglas production function with constant returns to scale [28]. The model is as stated below; Y = AK α L β (1) Where; Y is the total production (output), L is the Labor input, K is capital input and A is the total factor productivity, α and β are the output…”
Section: Model Specificationmentioning
confidence: 99%